Basics of geomatics - Gomarasca, Mario A. , 1954- (Springer, 2009)
"This volume presents a comprehensive and complete treatment. In a systematic way the complex topics and techniques are covered that can be assembled under Geospatial Information namely, Geodesy, Cartography, Photogrammetry, Remote Sensing, Informatics, Acquisition Systems, Global Positioning Systems, Digital Image Processing, Geographic Information Systems, Decision Support Systems, and WebGIS. It describes in detail and at an accessible level - too much math has been avoided - the state of current knowledge. Per chapter a detailed bibliography has been included." "As such, it will serve as a working tool not only to geoscientists and geographers but also to engineers, architects, computer scientists, urban planners, specialists in GIS, remote sensing, forestry, agricultural science, soil science geometry, environmental scientists and managers. Applications can be found in security, risk management, monitoring, info-mobility, geo-positioning, food traceability, etc."--Jacket